2008
DOI: 10.1002/aic.11624
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoresis of axisymmetric aerosol particles along their axes of revolution

Abstract: in Wiley InterScience (www.interscience.wiley.com).The axisymmetric thermophoretic motion of an aerosol particle of revolution in a uniformly prescribed temperature gradient is studied theoretically. The Knudsen number is assumed to be small so that the fluid flow is described by a continuum model. A method of distribution of a set of spherical singularities along the axis of revolution within a prolate particle or on the fundamental plane within an oblate particle is used to find the general solutions for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…That is, the effects of the four parameters k ‫ء‬ , C t ‫ء‬ , C m ‫ء‬ , and a / b on the thermophoretic mobility of a spheroid along its axis of revolution are opposite to those on the thermophoretic mobility of a spheroid normal to the axis. For the general problem of thermophoresis of a particle of revolution with fore-and-aft symmetry caused by a uniform temperature gradient in an arbitrary direction with respect to its axis of revolution, which is linear in its governing equations and boundary conditions, the solution of the thermophoretic velocity can be obtained by the vectorial addition of these previous results for the axial movement 44,45 and the present result for the transverse migration. …”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…That is, the effects of the four parameters k ‫ء‬ , C t ‫ء‬ , C m ‫ء‬ , and a / b on the thermophoretic mobility of a spheroid along its axis of revolution are opposite to those on the thermophoretic mobility of a spheroid normal to the axis. For the general problem of thermophoresis of a particle of revolution with fore-and-aft symmetry caused by a uniform temperature gradient in an arbitrary direction with respect to its axis of revolution, which is linear in its governing equations and boundary conditions, the solution of the thermophoretic velocity can be obtained by the vectorial addition of these previous results for the axial movement 44,45 and the present result for the transverse migration. …”
Section: Discussionmentioning
confidence: 79%
“…The thermophoresis of an axisymmetric aerosol particle with a temperature jump, a thermal slip, and a frictional slip at its surface along its axis of revolution was investigated by using a similar method of internal singularity distributions 44 and the corresponding motion of a prolate or oblate spheroid was also analyzed by using a method of separation or semiseparation of variables in spheroidal coordinates, 45 and analytical and numerical results of the thermophoretic mobil- ity for the particles with various values of aspect ratio were obtained. It was found that, for specified values of k ‫ء‬ , C t ‫ء‬ , and C m ‫ء‬ , the value of the normalized axisymmetric thermophoretic mobility U / U 0 of a spheroid in general increases with an increase in a / b, since the fraction of the thermal slip of the fluid at the particle surface in the direction along its axis of revolution increases with the increase of a / b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the remainder of the paper, for the sake of compactness, we will refer to this model simply as the 'NSF model with slip and jump'. In this case, for a spheroid of aspect ratio near one, an approximate solution was obtained by Senchenko and Keh (2007) with perturbation techniques and, for a spheroid of arbitrary aspect ratio, by Chang and Keh (2009a) using the singularity-collocation method. Two works for rarefied, confined flows in the plane are worthy of mention.…”
Section: Introduction 1preliminariesmentioning
confidence: 99%